HUBUNGAN ANTARA EFIKASI DIRI DAN MOTIVASI INTRINSIK DENGAN KREATIVITAS GURU PAUD - Roro Kurnia Nofita Rahmawati (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2020)
The purpose of this study was to examine the relationship between self efficacy and intrinsic motivation with the creativity of early child education teacher. Subjects were 100 early child education teachers in Pamekasan. The result of multiple regression analysis found the value of F=26,073 with p = 0,000 (p ≤ 0,01)thatself efficacy and intrinsic motivation had a significant correlation with the creativity of early child education teacher. It found that self efficacy and intrinsic motivation able to contribute positively to the creativity of early child education teacher of 35%. Result of parcial correlation between self efficacy with creativity of early child education teacher obtained by t = 2,970 and r parsial 0,294 with p = 0,004 (p ≤ 0,05), which showed a significant positively correlation betweenself efficacy with creativity of early child education teacher. Result of parcial correlation between intrinsic motivation with the creativity of early child education teacher obtained by t = 3,778 and r parsial 0,374 with p = 0,000 (p ≤ 0,01) which showed a very significant positively correlation between intrinsic motivation with the creativity of early child education teacher.